A New Educational Program could Reduce Disability and Improve Quality of Life in Patients with Chronic Low Back Pain - Tavafian, Sedigheh Sadat; Jamshidi, Ahmad Reza; Mohammad, Kazem (International Journal of Orthopedics and Rehabilitation, 2022)
This randomized clinical trial examined the efficacy of a designed educational program versus oral drug treatment in Iran. A total of 197 patients with chronic low back pain were randomized into either intervention group (n = 97) receiving a five 2 hour– session educational program followed by continued monthly booster sessions and telephone counseling plus medication or to control group (n = 100) receiving just medication. At baseline and 3 months of follow up, participants completed demographic characteristic questionnaires as well as three other questionnaires including Short – form General Health Survey (SF-36 item), Quebec Disability Scale (QDS) and Ronald – Morris Disability Questionnaire (RDQ). Data were analyzed by SPSS 18. The two groups were comparable at baseline in terms of all baseline characteristics and the mean scores of the scales. However, after three months, the intervention group was significantly different from control group in all subscales of SF-36, QDS and RDQ (P values < 0.05). Furthermore, this study showed a statistically significant difference between two groups (P< 0.05) in terms of mean difference scores for SF -36, RDQ and QDS over time. The findings revealed that the designed educational program could improve all quality of life domains and reduce disability in chronic low back pain patients during a period of 3 months.